1989
DOI: 10.1111/j.1365-246x.1989.tb00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Wave Propagation In A Vertical Transversely Isotropic Medium: Field Experiment and Model Study

Abstract: A down-hole experiment was carried out in the transversely isotropic Oxford Clay outcropping in the south of England. Different moveout curves for the two shear wave types and anomalous amplitude features for the SV-wave were found in the field data. Based on velocity measurements carried out formerly at the site a model study was performed to explain the results. Phase velocity and group velocity curves computed analytically with the method of characteristics, and synthetic seismograms computed with the Aleks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Crampin (1987) discussed the geological and industrial implications of EDA. In exploration studies (Helbig, 1984;Leary and Henyey, 1985;Kerner et al, 1989;Corrigan, 1989; and many others), the velocity anisotropy measured from travel times has suggested the presence of significant anisotropy in sedimentary basins.…”
Section: Introductionmentioning
confidence: 97%
“…Crampin (1987) discussed the geological and industrial implications of EDA. In exploration studies (Helbig, 1984;Leary and Henyey, 1985;Kerner et al, 1989;Corrigan, 1989; and many others), the velocity anisotropy measured from travel times has suggested the presence of significant anisotropy in sedimentary basins.…”
Section: Introductionmentioning
confidence: 97%
“…Volumes of inherently isotropic rocks may be microfractured by regional tectonic stresses, resulting in a system of oriented fractures along principal axes which could lead to global anisotropy (Bamford & Nunn 1979; Leary et al 1987). In exploration studies (Helbig 1984; Leary & Henyey 1985; Corrigan 1989; Kerner et al 1989, and many others), velocity anisotropy measured from traveltimes has suggested the presence of significant anisotropy in sedimentary basins. Similar results for Earth's crust and mantle have been obtained in earthquake studies (Gupta 1973; Crampin 1985; Thomsen 1986; and many others).…”
Section: Introductionmentioning
confidence: 99%
“…Single values are for normal to bedding unless marked with * indicating orientation is unknown. # saturated bulk density based on porosity and grain density ## saturated bulk density based on porosity and dry bulk density + extrapolated to zero confining stress $ computed using Poisson ratio and Young's modulus Jougnot et al (2010); (17) Burland et al (1977); (18) Ghorbani et al (2009);(19) Bastiens et al (2007); (20) Kerner et al (1989); (21) Niandou et al (1997) Similar data are available from Horsrud (2001), who also developed several correlations between sonic velocity and petrophysical parameters. These data are mainly from formations in the North Sea that are of interest for petroleum resource development.…”
Section: Data Used To Develop the Correlationsmentioning
confidence: 91%